Peran pemerintah, masyarakat dan daya tarik wisata terhadap revisit intention wisatawan pantai kota Pariaman - Afriyeni Afriyeni; Bakaruddin Bakaruddin; Sintia Safrianti (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2022)
The tourism industry is seen as a rapidly growing industry, where one of the main trends in the tourism market is beach tourism. The attractiveness of beach tourism will determine the occurrence of repeat visits from tourists to a tourist destination. This study was conducted to examine the role of government, community, and tourist attraction in the revisit intention of tourists with tourist attraction as a mediator. Respondents used as many as 296 people. Sampling with the convenience sampling method. The analytical model used in this research is Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the study indicate that the role of the government and the community has an impact on tourist attraction and revisit the intention of Pariaman beach tourists. In addition, the findings of this study also explain the mediating effect of the tourist attraction variable in the relationship between the role of the government and the role of the community on the revisit intention of tourists at Pariaman beach.